Pengelolaan Kehutanan Berbasis Masyarakat Hukum Adat dalam Kerangka Konstitusi Hijau di Indonesia - Chandra, Febrian (Adagium: Jurnal Ilmiah Hukum, 2025)
Forestry management in Indonesia has an important role in supporting the balance of ecosystems and community welfare. In recent decades, the issue of forest degradation and deforestation has become a serious concern, both at the national and international levels. The concept of the Green Constitution comes as an approach that emphasizes environmental protection within a strong legal framework. This research aims to ensure that natural resource management policies, including forestry, are carried out with the principles of sustainability and environmental responsibility. The research method used is a normative legal research method with a conceptual approach, the results of this study found that the green constitution can be applied in forestry management in Indonesia, as well as the challenges and opportunities faced in its implementation. This study examines various relevant legal and policy aspects, including the protection of indigenous peoples' rights, public participation mechanisms, and the responsibilities of the state and other stakeholders in preserving forests. Thus, it is hoped that forestry management in Indonesia can be more sustainable and fair, in line with the principles of the Green Constitution.